Pemberdayaan Karang Taruna dalam Pengembangan Ekosistem UMKM melalui Media Website di Desa Purworejo - Wenti Ayu Sunarjo; Wibowo, Ari Putra; Amalia Ilmiani; Audrey Elvina Khoirunnisa; Supajar Bayu Aji; Agus Setiawan; Wafa Khansa Fadhilah; Sara Silvia (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The community service program in Purworejo Village, Sragi District, Pekalongan Regency, was implemented to enhance the capacity of local MSME actors in utilizing digital technology as a modern marketing tool. The program adopted a participatory approach involving youth organizations, business actors, village authorities, and the implementation team in every stage of the activity. Assistance included field observation, data collection, content development training, and the creation of a dedicated MSME website as a shared promotional platform. The results indicate significant social changes within the community, including improved digital literacy, stronger awareness of the importance of technology-based marketing, the emergence of local youth as digital facilitators, and the development of collaborative working patterns in managing digital media. These findings reinforce that participatory-based mentoring can strengthen community capacity in adopting technology, consistent with theoretical perspectives that position the community as key agents of local development. Therefore, the program not only produced a functional digital product in the form of an MSME website but also laid the foundation for a more adaptive, competitive, and sustainable village economic ecosystem..